Standardized tools for assessing balance and mobility in stroke clinical practice guidelines worldwide: a scoping review (2023)
Background: Use of standardized tools to assess balance and mobility limitations is a recommended practice in stroke rehabilitation. The extent to which clinical practice guidelines (CPGs) for stroke rehabilitation recommend specific tools and provide resources to support their implementation is unknown. Purpose: To identify and describe standardized, performance-based tools for assessing balance and/or mobility and describe postural control components challenged, the approach used to select tools, and resources provided for clinical implementation, in CPGs for stroke. Methods: A scoping review was conducted. We included CPGs with recommendations on the delivery of stroke rehabilitation to address balance and mobility limitations. We searched seven electronic databases and grey literature. Pairs of reviewers reviewed abstracts and full texts in duplicate. We abstracted data about CPGs, standardized assessment tools, the approach for tool selection, and resources. Experts identified postural control components challenged by each tool. Results: Of the 19 CPGs included in the review, 7 (37%) and 12 (63%) were from middle and high-income countries, respectively. Ten CPGs (53%) recommended or suggested 27 unique tools. Across 10 CPGs, the most commonly cited tools were the Berg Balance Scale (BBS) (90%), 6-Minute Walk Test (6MWT) (80%), Timed Up and Go Test (80%) and 10-Meter Walk Test (70%). The tool most frequently cited in middle- and high-income countries was the BBS (3/3 CPGs), and 6MWT (7/7 CPGs), respectively. Across 27 tools, the three components of postural control most frequently challenged were underlying motor systems (100%), anticipatory postural control (96%), and dynamic stability (85%). Five CPGs provided information in varying detail on how tools were selected; only 1 CPG provided a level of recommendation. Seven CPGs provided resources to support clinical implementation; one CPG from a middle-income country included a resource available in a CPG from a high-income country. Conclusion: CPGs for stroke rehabilitation do not consistently provide recommendations for standardized tools to assess balance and mobility or resources to facilitate clinical application. Reporting of processes for tool selection and recommendation is inadequate. Review findings can be used to inform global efforts to develop and translate recommendations and resources for using standardized tools to assess balance and mobility post-stroke.